On the Hereditary Paracompactness of Locally Compact, Hereditarily Normal Spaces. Issue 3 (1st September 2014) - Larson, Paul; Tall, Franklin D.
Abstract: We establish that if it is consistent that there is a supercompact cardinal, then it is consistent that every locally compact, hereditarily normal space that does not include a perfect pre-image of \!\!ω\!\! _1 is hereditarily paracompact.